Finitely Generated Modules over Group Rings of a Direct Product of Two Cyclic Groups. (1st December 2014) - Najim, Ahmed; Charkani, Mohammed Elhassani
Abstract : Let K be a commutative field of characteristic p > 0 and let G = G 1 × G 2, where G 1 and G 2 are two finite cyclic groups. We give some structure results of finitely generated K [ G ] -modules in the case where the order of G is divisible by p . Extensions of modules are also investigated. Based on these extensions and in the same previous case, we show that K [ G ] -modules satisfying some conditions have a fairly simple form.